Kehangatan Hubungan dengan Orang Tua, Pengasuh dan Teman dengan Sindrome Depresi pada Remaja Panti Asuhan di Jakarta - Nesi Sulaiman (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2019)
Depression is a mental health problem caused by multifactors and is common in adolescents. Adolescents who live in orphanages are considered vulnerable to the appearance of depression. Even so, adolescents who live in orphanages in Jakarta generally still have parents so they can establish a warmth relationship as protection against depression syndrome. In addition to parents, adolescents who live at the Orphanage also establish warmth relationships with friends and caregivers. This research was conducted to find out how the warmth of adolescent relationships with parents, caregivers and friends with depression syndrome among adolescents in orphanages. This study was conducted in 402 adolescents (male: 179; female: 223; M: 14.88) in 20 orphanages in Jakarta. The results of the study show the warmth of relationships with mothers, fathers, caregivers and friends in adolescents at the middle level and symptoms of depression at low levels. Furthermore, this study found that only the warmth of the relationship with the father correlated with depression syndrome.